Quantifying spatiotemporal patterns and influencing factors of urban shrinkage in China within a multidimensional framework:A case study of the Yangtze River Economic Belt. (April 2023) - He, Xiujuan; Guan, Dongjie; Zhou, Lilei; Zhang, Yuxiang; Gao, Weijun; Sun, Lingli; Huang, Danan; Li, Zihui; Cao, Jiameng; Su, Xiangyuan
Highlights: Urban shrinkage at regional scales is characterized by greater complexity. Shrinking types are distinguished based on degree, trajectory and dimensionality. The heterogeneity of shrinkage in sub-region of the riverine area is significant. A multi-level managing system is essential for the upper, middle and lower reaches. Abstract: Explorations of urban shrinkage at regional scales have received much attention around the world. The Yangtze River Economic Belt (YREB), one of the most influential inland river economic belts in the world, has not yet received sufficient attention to its urban shrinkage issue. This study explored the spatiotemporal patterns and influencing factors of shrinking cities in the YREB within a multidimensional framework, including population, economy, and space. The results showed that the degree of demographic, economic, and spatial shrinkage is mainly slight or moderate in the YREB. In terms of shrinking duration, these shrinking cities mainly undergo temporary shrinkage. The majority of cities undergo shrinkage in only one dimension, accounting for more than 62% of all shrinking cities. The spatial heterogeneity of shrinking cities mainly comes from within reaches and urban agglomerations, while there is little difference in shrinkage between reaches and between urban agglomerations. Fixed asset investment, total social consumption, the industrial output value above the scale, and the built-up area had significant impacts on the population agglomeration, economic agglomeration, and public service accessibility of multidimensionally shrinking cities. The spatiotemporal heterogeneity and dynamics of shrinkage suggest that a multi-level management system should be constructed to cope with urban shrinkage in different regions of the YREB. This study can provide a reference for narrowing the developmental imbalance for the YREB and contributes to promoting the research progress of urban shrinkage at regional scales.